Fabrication of Functionalized MOFs Incorporated Mixed Matrix Hollow Fiber Membrane for Gas Separation - Haitao Zhu; Xingming Jie; Yiming Cao (Journal of Chemistry)
The metal-organic framework (MOFs) of MIL-53 was functionalized by aminosilane grafting and then incorporated into Ultem®1000 polymer matrix to fabricate mixed matrix hollow fiber membrane (MMHFM) with high separation performance. SEM, XRD, and TGA were performed to characterize the functionalized MIL-53 and prepared MMHFM. The filler particles were embedded in membrane successfully and dispersed well in the polymer matrix. The incorporation of MOFs endowed MMHFM better thermal stability. Moreover, effects of solvent ratio in spinning dope, spinning condition, and testing temperature on gas separation performance of MMHFM were investigated. By optimizing dope composition, air gap distance, and bore fluid composition, MMHFM containing functionalized MIL-53 achieved excellent gas permeance and CO2/N2 selectivity. The CO2 permeance increased from 12.2 GPU for pure Ultem HFM to 30.9 GPU and the ideal CO2/N2 selectivity was enhanced from 25.4 to 34.7 simultaneously. Additionally, gas permeance increased but the selectivity decreased with the temperature increase, which followed the solution-diffusion based transport mechanism.